The effect of prostate cancer on endurance exercise capacity in the rat - Esau, Peter John (Kansas State University, 2016)
Cancer patients have a reduced exercise capacity compared to age-matched healthy counterparts which contributes to premature fatigue. The reductions in exercise capacity are multifactorial and vary depending on the type of treatments and the specific cancer. Given that cancer treatments have been shown to impair cardiovascular and/or skeletal muscle function, it is difficult to determine if cancer itself reduces exercise capacity. We used a rat prostate tumor model to test the hypothesis that cancer independently reduces endurance exercise capacity. Methods: In male Copenhagen rats (COP/CrCrl), an initial treadmill test to exhaustion was used to determine endurance exercise capacity. Subsequently, the prostates of the rats were injected with either prostate carcinoma cells (R-3327 AT-1) in Matrigel (cancer: n = 9) or Matrigel only (sham: n = 7). Treadmill tests to exhaustion were repeated four and eight weeks post-surgery. Results: Time to exhaustion decreased over the course of the experimental protocol in both the sham and cancer groups. However, the overall reduction in time to exhaustion in the cancer group (-16.7 ± 1.9 min) was significantly greater (p = 0.038) than the sham group (-10.1 ± 2.2 min). Despite no differences in total body mass at the end of the experimental protocol, heart, left ventricle, and gastrocnemius muscle mass were significantly lower in the cancer group compared to the sham group (p < 0.05 for all). Moreover, within the cancer group heart and left ventricle mass, but not gastrocnemius mass, were significantly inversely correlated with prostate tumor mass. Conclusion: Endurance exercise capacity was reduced in rats with untreated prostate cancer to a greater extent than it was reduced in sham operated rats. Although multiple mechanisms likely contributed to the reduced exercise capacity, reductions in heart and gastrocnemius muscle mass likely played an important role.
Keywords: Prostate cancer; Exercise capacity; Endurance exercise